A decision support system for Parkinson disease management: expert models for suggesting medication change. (15th May 2018) - Bohanec, Marko; Miljković, Dragana; Valmarska, Anita; Mileva Boshkoska, Biljana; Gasparoli, Elisabetta; Gentile, Giovanni; Koutsikos, Konstantinos; Marcante, Andrea; Antonini, Angelo; Gatsios, Dimitrios; Rigas, George; Fotiadis, Dimitrios I.; et al.
Abstract: Parkinson's disease (PD) is a degenerative disorder of the central nervous system, which requires a long-term, interdisciplinary disease management. The EU Horizon 2020 project PD_manager (http://www.parkinson-manager.eu/ ) is aimed at developing a decision support system for PD management. As part of this task, we have developed decision-support models that identify situations in which the disease has progressed to the point which requires a change of medical therapy. The input data includes motor symptoms, non-motor symptoms and epidemiologic data. The models were developed in collaboration with medical experts, using a qualitative multi-criteria method DEX. In this paper, we describe the process and results of model development, and assess the quality of models in terms of classification accuracy, transparency, correctness and completeness.